Nationally executed programme/project management - Mercado, Cesar Matamorosa 1938- (Quezon City Development Consultants for Asia Africa Pacific, 2004)
Purpose: "The purpose of this handbook is to help national and international project managers and staff and other interested parties understand and appreciate the new modality in executing UN-assisted programmes/projects." The handbook focuses primarily on the new Nationally Executed Programme/Project concepts, principles, paradigms, structures and activities."
Content/s: Basic Programme/Project concepts, paradigm and process. National Execution Concepts and Practices. National Execution Structures and Procedures. Development and Management of Nationally Executed Projects. Mobilization of Nationally Executed Projects. Monitoring, Evaluation and Reporting.
Condensed from UNDP and UNFPA documents.
Keywords: Project management -- Handbooks, manuals, etc; participatory monitoring and evaluation (Project management) -- Handbooks, manuals, etc